Quick Large-Area Detection of Thin Silicone Films with Coherent Raman Scattering Imaging - Naser, Julian; Sarau, George; Wrege, Jan; Schmidt, Michael; Christiansen, Silke (physica status solidi (a), 2024)
Coherent Raman Scattering Imaging offers quick and surface-sensitive large-area scans of specimens including fingerprinting of the substances, combined with low detection limits. By using a multi-photon process, it offers orders of magnitude stronger surface signal in comparison to spontaneous Raman (SR) and fluorescence signals of the substrate are avoided by the detection principle and the near-infrared laser wavelength. By exciting at a specific wavelength instead of measuring whole spectra the measurement time is remarkably reduced. Here, detecting organic thin films on glass surfaces is investigated. The detection of those thin films is relevant for production processes where the interfacial layer is influenced by the low surface energy of contaminants, especially polysiloxanes. The samples are manufactured by pipetting diluted polydimethylsiloxane (PDMS) in heptane in various concentrations (1%, 0.1%, 0.01%, and 0.001%) on glass substrates. After evaporation of the solvent, thin films of the silicone remain. The resulting average coverage of the thin films equals 100–0.1 μg cm−2. Measurements determine the detectability threshold with SR to 10 μg cm−2, while the acquired spectrum is used to determine characteristic peaks for the pump laser. Afterwards the samples are imaged at those wavenumbers with Coherent Raman Scattering (CRS) Imaging techniques providing a chemically-specific contrast.
CRIS-Team Scopus Importer:2024-03-15
Keywords: cars; contamination monitoring; raman; silicone; srs; thin film detection